Effects of volume-based overload plyometric training on maximal-intensity exercise adaptations in young basketball players - Asadi, A.; Ramirez-Campillo, R.; Meylan, C.; Nakamura, F. Y.; Cañas-Jamett, R.; Izquierdo, M. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: The aim of the present study was to compare maximal-intensity exercise adaptations in young basketball players (who were strong individuals at baseline) participating in regular basketball training versus regular plus a volume-based plyometric training program in the pre-season period.